Implementation of Catur Purusa Artha in Village Credit Institution’s Financial Management - Ida Bagus Anom Purbawangsa; Henny Rahyuda; Ketut Arya Bayu Wicaksana (Universitas Pendidikan Ganesha, 2023)
This study delves into the implementation of Catur Purusa Artha in managing the finances of Village Credits Institutions. Defining Dharma as adherence to rules, Artha as the pursuit of profits, Kama as efforts towards development, and Moksha as endeavors for harmony with stakeholders, the research explores these principles across 40 Village Credit Institutions (LPD). Data, collected through questionnaires and analyzed using frequency distribution techniques, provides insights into the incorporation of these concepts. Triangulation strengthens findings through comparisons with in-depth interviews of two LPD informants outside the sample group. The results reveal that all respondents implement the Catur Purusha Artha concept. However, a nuanced analysis highlights areas for improvement, specifically in lending activities and product development. This study indicates a fusion of traditional and modern management approaches within LPDs, showcasing a dynamic blend of principles that contribute to their financial management. These findings offer valuable insights for enhancing the effectiveness of Village Credit Institutions by addressing specific areas requiring attention and emphasizing the coexistence of traditional and contemporary management practices in LPDs.